Effect on longevity of one-third reduction in premature mortality from non-communicable diseases by 2030: a global analysis of the Sustainable Development Goal health target. Issue 12 (December 2018) - Cao, Bochen; Bray, Freddie; Ilbawi, André; Soerjomataram, Isabelle
Summary: Background: To curb the rising global burden of non-communicable diseases (NCDs), the UN Sustainable Development Goals (SDGs) include a target to reduce premature mortality from NCDs by a third by 2030. A quantitative assessment of the effect on longevity of meeting this target is one of the many important measures needed to advocate and inform national disease control policies. We did a global analysis to estimate improvements in average expected years lived between 30 and 70 years of age that would result from meeting the SDG target. Methods: We estimated age-specific mortality in 183 countries in 2015, for the four major NCDs (cardiovascular diseases, cancers, chronic respiratory diseases, and diabetes) and all NCDs combined, using data from WHO Global Health Estimates. We then estimated the potential gains in average expected years lived between 30 and 70 years of age (LE[30–70) ) by eliminating all or a third of premature mortality from specific causes of death in countries grouped by World Bank income groups. The feasibility of reducing mortality to the targeted level over 15 years was also assessed on the basis of historical mortality trends from 2000 to 2015. Findings: Reducing a third of premature mortality from NCDs over 15 years is feasible in high-income and upper-middle-income countries, but remains challenging in countries with lower income levels. National longevity will improve if this target is met, corresponding to an average gain in LE[30–70) of 0·64 years worldwide from reduced premature mortality for the four major NCDs and 0·80 years for all NCDs. According to major NCD type, the largest gains attributable to cardiovascular diseases would be in lower-middle-income countries (a gain of 0·45 years), whereas gains attributable to cancer would be in low-income countries (0·33 years). Interpretation: A one-third reduction in premature mortality from the major NCDs in 2015–30 would have substantial effects on longevity. High-level political commitments to effective and equitable national surveillance and prioritised prevention, early detection, and treatment programmes tailored to the major NCD types are needed urgently in lower-resourced settings if this SDG target is to be met by 2030. Funding: None.